Globalisation of Engineers: African Professional Engineering Education Perspectives - Matemba, Esther Elly (Curtin University, 2020)
This thesis contributes an African engineering education perspective to the topic on developing global engineers. It poses the argument that the existing discourse is founded on the Global North perspective of engineering education, and that it does not speak from the actual situation that exists in most Africa countries. Using data from Tanzania, and applying Bourdieu's theory of practice, this research addresses the relevance of the existing discourse for developing global engineers in Africa.